2002
DOI: 10.1081/pdt-120015048
|View full text |Cite
|
Sign up to set email alerts
|

Preformulation Studies and Characterization of Proposed Chondroprotective Agents: Glucosamine HCl and Chondroitin Sulfate

Abstract: The physicochemical and mechanical characteristics between the various dietary supplements studied varied greatly. Data obtained from this study provide an understanding of the physicomechanical behavior of chondroitin sulfate and glucosamine HCl. Application of this knowledge would facilitate development of stable solid dosage forms containing these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The observed deformation characteristics (plastic flow) for all samples used may be due to the extreme hygroscopic and deliquescent nature of the extract. This is because earlier report had indicated that the deformation characteristics for all samples of the extremely hygroscopic and deliquescent chondroitin sulfate were by plastic flow 14 . The increase in slope at higher pressure indicates an increase in the rate of densification as the void spaces between particles decrease.…”
Section: Fig 1: Heckel Plots For Evg Compacts Produced Using Selectementioning
confidence: 86%
“…The observed deformation characteristics (plastic flow) for all samples used may be due to the extreme hygroscopic and deliquescent nature of the extract. This is because earlier report had indicated that the deformation characteristics for all samples of the extremely hygroscopic and deliquescent chondroitin sulfate were by plastic flow 14 . The increase in slope at higher pressure indicates an increase in the rate of densification as the void spaces between particles decrease.…”
Section: Fig 1: Heckel Plots For Evg Compacts Produced Using Selectementioning
confidence: 86%